Ore Remobilization History of the Metamorphosed Rävliden North Volcanogenic Massive Sulfide Deposit, Skellefte District, Sweden - Rincon, Jonathan; Jansson, Nils; Thomas, Helen; Kaiser, Majka Christiane; Persson, Mac Fjellerad; Nordfeldt, Erik; Wanhainen, Christina (Economic Geology, 2024)
The Skellefte district in northern Sweden hosts many volcanogenic massive sulfide (VMS) deposits and is considered one of the most important European mining districts for Cu, Zn, Pb, Ag, and Au. The volcanic and sedimentary rocks that the VMS deposits are hosted in were deformed during the Svecokarelian orogeny, with three documented regional deformation phases. These events imparted a distinct attitude and geometry to the deposits, their host succession, and discordant zones of synvolcanic hydrothermal alteration. Few studies have investigated the detailed deformation effects on the sulfide minerals. In this contribution, we document the structural characteristics and remobilization history of mineralization at the Rävliden North Zn-Pb-Cu-Ag deposit—one of the most important recent discoveries in the district consisting of 8.5 million tonnes (Mt) grading 1.01% Cu, 3.45% Zn, 0.53% Pb, 78.60 g/t Ag, and 0.23 g/t Au. At Rävliden, massive to semimassive sphalerite-rich mineralization with lesser pyrrhotite, galena, pyrite, and silver minerals occurs structurally above stringer-type mineralization dominated by chalcopyrite, pyrrhotite, and pyrite. These mineralization types exhibit evidence of deformation and remobilization such as (1) sulfide-alignment parallel to tectonic foliations; (2) rounded wall-rock tectonoclasts in a ductile deformed sulfide matrix (“ball ore” or durchbewegt ore); and (3) sulfides in tension gashes, strain shadows, piercement veins, and late, straight veinlets crosscutting tectonic fabrics. These features are attributed to polyphase deformation during the D1, D2, and D3 events at temperature ranging from 200° to 550°C. Remobilization of sulfides was mostly within the bounds of the main mineralization (i.e., 10–100 m), with few local external occurrences. A combination of solid-state and fluid-assisted remobilization processes are inferred. Rare brittle veinlets and zeolite-cemented breccias with sphalerite, galena, and silver minerals occur in the stratigraphic hanging wall, where they ...